Clinical and functional outcomes of tarsal coalition resection to correct rigid flat foot - Guimarães Huyer, Rodrigo; Cillo, Mário Sérgio Paulillo; Castro Filho, Carlos Daniel Cândido; Bertelli, Hallan Douglas; Girondo, Marcelo Morelli; Bortolatto Neto, Armando (Journal of the Foot & Ankle, 2021)
Objective: This study used the AOFAS score to assess the clinical functional results of patients who underwent tarsal coalition resection. Methods: This was a retrospective case series of patients who underwent tarsal coalition resection to correct rigid flat foot. Clinical and functional assessment was performed with the AOFAS score before and 6 months after surgical treatment. Descriptive analysis was performed for 7 patients (11 operated feet) using measurements of position and dispersion (mean, standard deviation, minimum, median and maximum value) for continuous variables and frequency tables (absolute and relative) for categorical variables. Results: The mean patient age was 10 years, 7 months, and the majority (71.43%) were male. The most affected joint was the calcaneonavicular. The right side was affected in 54.55% of the cases. The most frequent type of coalition was osseous (81.82% of the cases). The mean pre- and postoperative AOFAS scores were 32.7 and 70.2 points, respectively, which was a significant increase. Conclusion: The increased scores after coalition resection was considered the main change between the two assessments. Thus, it can be concluded that in rigid flat feet without severe hind- or forefoot deformities for which conservative treatment failed, bar resection should be the surgical procedure of choice. Level of Evidence IV; Therapeutic Studies; Case Series.